Recent Study on Theoretical Foundation of a Human-Techno-Structural Model of Managerial Competencies for the Public Transport of Dry Cargo - Eduardo Cruz Aldana; Antonio Oswaldo Ortega Reyes; Jaime Garnica González; Eva Selene Hernández Gress; Carlos Robles Acosta; Octavio Castillo Acosta; Hector Rivera Gómez; Oscar Montaño Arango; José Ramon Corona Armenta; Mariana Marcelino Aranda (New Ideas Concerning Science and Technology Vol. 10, 2021)
This paper presents a proposal of the theoretical and contextual foundation of a human techno structural model (HTSM) of managerial competencies of dry cargo auto transportation (DPCAT) in Mexico. Firstly, the conceptualization of state of the art is shown through the analysis of the theoretical framework concerning management skills models and, as a second element, an analysis of the contextual framework of applied management skills certification models was shown currently in the DPCAT sector to integrate them into the decision making the process of managers in the metropolitan area of the state of Hidalgo, in 2016. This also shows the results obtained from the application of a questionnaire that relates the managerial competencies with the expected performances and the results of this, which was the base the techno structural approach and its relation to the individual needs of the manager, giving rise to a standardization proposal based on Leadership, Diagnostics of competencies, Installation of competencies, Development of competencies and Enhancement of competencies. This development establishes that personal changes (directive) and interference in group changes are accompanied by a cognitive and experiential process that ensures the self-sustaining of HTSM in the organization.